Conceptual framework on understanding the behavioural intention and usage of indonesian tourists in relation to the digital payment system: an analysis of UTAUT2 / Muhammad Zainul Ridho, Faiz Izwan Anuar and Nur Alissya Nazri - Ridho, Muhammad Zainul; Anuar, Faiz Izwan; Nazri, Nur Alissya (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
This research examines the crucial area of digital payment uptake among Indonesian visitors in Malaysia, providing a thorough and strong research approach. This research investigates the key aspects that impact the decisions made regarding digital payment systems, providing a clear understanding of their measurable impact on usage. The research method utilizes a quantitative approach and a carefully planned non-probability sampling procedure and uses purposive sampling is sampling technique use with the aid of G*Power software, guaranteeing accuracy and statistical rigor. Utilizing the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) as a theoretical framework, the study examines eight determinants: Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Facilitating Conditions (FC), Privacy, Security, Price Value, and Awareness. This research aims to examine the determinants that influence Indonesian tourists' inclination to utilize digital payment systems while visiting Malaysia. Additionally, it seeks to assess the practical implementation of these intentions. By doing so, this research not only enhances our comprehension of this subject but also offers valuable empirical insights. By utilizing a minimum sample size of 172 respondents, the results are expected to possess not only informative value but also statistical significance, making a substantial contribution to the academic discussion on the topic.